Private equity challenge - Kompuestos as an investment opportunity in the plastic industry - Popa, Corina (2021)
This Private Equity project studies the benefits for a private equity firm of acquiring Kompuestos, a producer of masterbatches and other plastic compounds, aiming to adapt its business to meet current sustainability concerns and become more sustainable. The investment yields a 3.3x money multiple. Founded in 1986, Kompuestos is a Spanish player benefiting from a large and diversified client base, with annual turnover of € 46.2m and an EBITDA of € 3.3m. The plastics market is expected to reach a value of $ 721bn by 2025, with high growth opportunities coming from new segments including bioplastics and biodegradable solutions